(untitled) (Nigerian Journal of Pharmaceutical Research, 2023)
Background: Over the years, the scope of practice for the pharmacy profession has considerably broadened and several practice areas can now be chosen by young pharmacy graduates. However, not much is known about the career preferences of Nigerian pharmacy students. Objectives: To explore factors influencing the choice of a pharmacy degree, career preferences and perceptions of pharmacy practice areas in final year pharmacy students at selected universities in Northern Nigeria. Methods: A cross sectional study using a structured paper-based questionnaire to collect data from consenting students of six Northern Nigerian universities, was conducted from May to August 2021. Descriptive statistics were used to report the results obtained. Results: A total of 226 questionnaires were retrieved. Many of the respondents were male (57.5%) and studying for the Bachelor of Pharmacy degree (88%). Pharmacy was the first-choice course of study for almost 70% of the respondents, and the most common factors influencing their choice were personal interest (59.7%) and good job prospects (50.4%). Majority of respondents perceived that community pharmacy practice would provide them with the most financially rewarding career (32.7%), best work environment (33%) and best job opportunities (20%). Most of them also perceived themselves as having a heavy workload if they worked in hospital pharmacy (47.8%) and the best work schedule if they worked in academia (28.9%). Respondents’ top four career choices were community pharmacy, hospital pharmacy, public health pharmacy and industrial pharmacy. Conclusion: This study identified factors influencing the choice of a pharmacy degree and career preferences of respondents. Structured career counselling for young pharmacists is recommended.